2016
DOI: 10.1177/0969733015584966
|View full text |Cite
|
Sign up to set email alerts
|

Solving work-related ethical problems

Abstract: In the future, nurse managers need a more systematic approach to solve ethical problems. It is important to establish new kinds of ethics structures in organizations, such as a common, systematic ethical decision-making model and an ethics club for nurse manager problems, to support nurse managers in solving work-related ethical problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…The disciplinary decisions showed that organizational supervision varied, nurse managers has a central role in the process but very little detail was documented. In line with earlier studies, nurse managers had used a number of methods to tackle work-related problems (Aitamaa et al, 2019;Laukkanen et al, 2016). Our findings showed that the majority of these supervision procedures involved terminating the nurse's working contract.…”
Section: Systematic Structures For Organizational Supervisionsupporting
confidence: 87%
“…The disciplinary decisions showed that organizational supervision varied, nurse managers has a central role in the process but very little detail was documented. In line with earlier studies, nurse managers had used a number of methods to tackle work-related problems (Aitamaa et al, 2019;Laukkanen et al, 2016). Our findings showed that the majority of these supervision procedures involved terminating the nurse's working contract.…”
Section: Systematic Structures For Organizational Supervisionsupporting
confidence: 87%
“…Therefore, at the moment, it may seem that healthcare professionals do not suffer from burnout, but if these consequences of moral distress are underestimated and not addressed in a timely manner, they might do so in the future. Healthcare professionals, 45 47 including leaders and managers, 48 , 49 face many ethical dilemmas, problems and challenges in their daily work. Research has reported several situations where individual professionals are faced with unethical behaviour of others, or witness abuse or neglect committed by professionals in healthcare settings (older people care settings), 50 by other patients (in care homes for people with memory disorders) or by family members (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…NMs have identified some activities they use to solve work-related ethical problems: using discussion, cooperation, the work organisation, intervention, personal values, an operational model, statistics and feedback, and personal examples. Discussion and cooperation were the most commonly used activities [7]. When solving ethical problems, NMs’ own personal values have been found to be the most useful aid [810], or at least among the three most useful ones [7, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Discussion and cooperation were the most commonly used activities [7]. When solving ethical problems, NMs’ own personal values have been found to be the most useful aid [810], or at least among the three most useful ones [7, 10]. Discussions are also among the most frequently used resources in ethical problem-solving [7, 10, 11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation